Evaluasi Kinerja Cooling Tower Tipe Counter Flow Mechanical Induced Draft pada Pembangkit Listrik Tenaga Panas Bumi (Studi Kasus: PT Pertamina Geothermal Energy (Tbk), Area Ulubelu, Unit 4) - Agus Apriyanto; Amrul; Hadi Prayitno; Hafizd Zakiyun Al Rasyid (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
The cooling tower is one of the vital components in a Geothermal Power Plant (PLTP) system, functioning to cool the condensate water from the condenser before it is reused. This study aims to analyze the effectiveness of a counter flow mechanical induced draft cooling tower at PLTP Unit 4, PT Pertamina Geothermal Energy (Tbk), Ulubelu Area. The data were obtained from field measurements conducted over seven days at fourtime intervals each day. The parameters analyzed include range, approach, and effectiveness, calculated using inlet water temperature, outlet water temperature, and wet bulb temperature. The results show an average effectiveness value of 70.05%, with variations influenced by changes in range and approach values. This effectiveness is close to the design standards stated in the manufacturer’s specifications, indicating that the cooling tower operates with good performance. This analysis provides an overview of the actual equipment condition and can serve as a reference for maintenance and performance optimization in the future.